The Effects of Covid-19 in Respiratory Functions and Exercise Capacity: A Pilot Study in Young Adults - Akinci, Buket; Kaya, Begum Kara; Kisa, Eylul Pinar; Kocyigit, Ahmet; Hosbay, Zeynep; Ozdincler, Arzu (Global Journal of Respiratory Care, 2021)
Background: The impact of coronavirus (COVID-19) on the pulmonary system and exercise capacity of young adults is important in terms of early detection of the existing or future chronic disease risk and secondary prevention. Objective: To compare the respiratory functions and exercise capacity of young adults who recovered from COVID-19 with healthy peers. Methods: Fifteen individuals (7 male, 8 female) aged 18-25 years, diagnosed with COVID-19 and at least 8 weeks passed after diagnosis (mean time: 239.13±135.77 days; min-max: 67-494 days) were included in the study. Age-sex matched 14 individuals (6 males, 8 females) without any diagnosis of COVID-19 and not been under quarantine because of COVID-19 were invited to the study as a control group. Respiratory functions (FEV1, FVC, FEV1/FVC, PEF) and mouth pressures (maximal inspiratory pressure-MIP, maximal expiratory pressure-MEP) were. Submaximal exercise capacity was evaluated with the “6-minutes walking test”. The lower extremity muscle functions were determined with the “1-minute sit to stand test". Results: All subjects were treated at home and fatigue (46%), persistent (40%) cough were the most reported ongoing symptoms in subjects who had COVID-19. Ground-glass appearance consistent with viral pneumonia was detected in radiological imaging of 3 (20%) subjects. The 6-minutes walking distance (p=0.037) and the number of sit-stands for 1 minute (p=0.007) were significantly lower in patients who had COVID-19 than age-gender matched healthy controls. Conclusion: The results of our study show that exercise capacity and muscle strength may be affected in young adults with mild COVID-19 compared to their peers.